Tinjauan Hukum Internasional HAM dan Hukum Islam terhadap LGBT Perspektif Human Dignity Mashood A. Baderin - Abu Dzarrin al-Hamidy (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
This article deals with the issue of homosexuality from the perspective of human rights international law and Islamic law, particularly in the view of Mashood Baderin. The result of understanding towards human rights international law as well as towards Islamic law as the blessings for the universe places human beings in the most respected position. However, there emerge the phenomenon of non-mainstream sexual orientation, such as lesbian, gay, bisexual and transgender (LGBT). In the perspective of Mashood Baderin, who portrays human rights international law and Islamic law on the principles of equality and justice, these LGBTs have their rights, as they are also human beings that should be respected due to their human dignity. It is inhumane to discriminate and condemn them. They should receive proportional treatment from the state so that their civil rights are guaranteed. However, with regard to their sexual orientation Islamic law prohibits the same sex marriage or other forbidden sexual relations